ECONOMIC EFFICIENCY OF CATTLE PRODUCTION IN THE BRAZILIAN AMAZON - Marcos Antônio Souza dos Santos; Antônio Cordeiro de Santana; Alfredo Kingo Oyama Homma; Andréia Santana Bezerra; José de Brito Lourenço Júnior (International Journal of Food and Agricultural Economics, 2019)
The article estimates a production function for cattle raising developed in the municipalities of the Brazilian Amazon, aiming to identify the influence of production factors on cattle production value. Municipal data on the gross value of cattle production, pasture areas, labor employed in livestock production, value of livestock investments, and access to technical assistance services were used. The model was statistically significant, and the production factors explained 84.54% of the changes in cattle production value. Land and capital factors contributed the most to the determination of production value. On the other hand, labor contributed the least. Cattle production shows increasing returns to scale, indicating the possibility of reducing average production costs by intensifying the use of the available production factors.